Exploiting β‐Lactams‐Induced Lysis and DNA Fragmentation for Rapid Molecular Antimicrobial Susceptibility Testing of Neisseria Gonorrhoeae via Dual‐Digital PCR - Jiumei Hu; Liben Chen; Pengfei Zhang; Fan‐En Chen; Hui Li; Kuangwen Hsieh; Sixuan Li; Johan H. Melendez; Tza‐Huei Wang (Advanced Science)
Abstract The evolution of antimicrobial resistance (AMR) presents substantial challenges to global medical health systems. Neisseria gonorrhoeae (N. gonorrhoeae), in particular, has developed resistance to all currently available antimicrobials. Addressing this issue necessitates not only discovering new antimicrobials but also deepening the understanding of bacterial responses to these agents, which can lead to new markers for rapid antimicrobial susceptibility testing (AST). Such advancements can enhance treatment outcomes and promote antimicrobial stewardship. In this study, single‐cell techniques, including live‐cell imaging, flow cytometry, and digital polymerase chain reaction (PCR) are utilized, to investigate the lysis dynamics and molecular features of N. gonorrhoeae upon exposure to β‐lactam antimicrobials. Distinct patterns of bacterial lysis and DNA fragmentation are uncovered in susceptible strains. Leveraging these discoveries, a microfluidic dual‐digital PCR approach that combines single‐cell and single‐molecule analyses, facilitate rapid and efficient phenotypic molecular AST for N. gonorrhoeae against β‐lactams is developed. This proof‐of‐concept validation demonstrates the effectiveness of the method in accessing antimicrobial susceptibility across a range of bacterial strains, contributing valuable insights for advancing the battle against AMR.